Therapeutic Potential of Selectively Targeting the α2C-Adrenoceptor in Cognition, Depression, and Schizophrenia—New Developments and Future Perspective - Uys, Madeleine Monique; Shahid, Mohammed; Harvey, Brian Herbert (Frontiers in Psychiatry, 2017)
α2A- and α2C-adrenoceptors (AR) are the primary α2-AR subtypes involved in central nervous system (CNS) function. These receptors are implicated in the pathophysiology of psychiatric illness, particularly those associated with affective, psychotic and cognitive symptoms. Indeed, non-selective α2-AR blockade is proposed to contribute towards antidepressant (e.g. mirtazapine) and atypical antipsychotic (e.g. clozapine) drug action. Both α2C- and α2A-AR share auto-receptor functions to exert negative feedback control on noradrenaline (NA) release, with α2C-AR heteroreceptors regulating non-noradrenergic transmission (e.g. serotonin, glutamate). While the α2A-AR is widely distributed throughout the CNS, α2C-AR expression is more restricted, suggesting the possibility of significant differences in how these two receptor subtypes modulate regional neurotransmission. However, the α2C-AR plays a more prominent role during states of low endogenous NA activity, whilst the α2A-AR is relatively more engaged during states of high noradrenergic tone. Although augmentation of conventional antidepressant and antipsychotic therapy with non-selective α2-AR antagonists may improve therapeutic outcome, animal studies report distinct yet often opposing roles for the α2A- and α2C-ARs on behavioural markers of mood and cognition, implying that non-selective α2-AR antagonism may compromise therapeutic utility both in terms of efficacy and side-effect liability. Recently several highly selective α2C-AR antagonists have been identified that have allowed deeper investigation into the function and utility of the α2C-AR. ORM-13070 is a useful positron emission tomography (PET) ligand, ORM-10921 has demonstrated antipsychotic-, antidepressant and pro-cognitive actions in animals, while ORM-12741 is in clinical development for the treatment of cognitive dysfunction and neuropsychiatric symptoms in Alzheimer’s disease. This review will emphasize the importance and relevance of the α2C-AR as a neuropsychiatric drug target in major depression, schizophrenia and disorders of cognition. In addition, we will present new prospects and future directions of investigation.